2014
DOI: 10.1038/jcbfm.2014.180
|View full text |Cite
|
Sign up to set email alerts
|

SUMO2/3 is Associated with Ubiquitinated Protein Aggregates in the Mouse Neocortex after Middle Cerebral Artery Occlusion

Abstract: Protein modifications cooperatively act to protect the proteome from cellular stress. Focal cerebral ischemia increases protein ubiquitination, resulting in formation of ubiquitin-rich aggregates. A concurrent elevation in small ubiquitin-related modifier (SUMO)-conjugated proteins has also been reported, but a potential connection to ubiquitin remains unexplored. Here we show that SUMO2/3 conjugates are present in postischemic ubiquitin-rich aggregates, physically associated with ubiquitin. The coaggregation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 15 publications
5
59
2
Order By: Relevance
“…Relatively few previous efforts to make a T1 agent for this application have been made [4,6,15], and to our knowledge, none have yet been successful in imaging plaques in vivo following intravenous injection. Kim et al demonstrated [10,11,16] a hollow manganese oxide nanoparticle targeted using the amyloid peptide as a targeting ligand. It was delivered by intracranial injection into the cisterna magna and did not have to negotiate the blood-brain barrier.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively few previous efforts to make a T1 agent for this application have been made [4,6,15], and to our knowledge, none have yet been successful in imaging plaques in vivo following intravenous injection. Kim et al demonstrated [10,11,16] a hollow manganese oxide nanoparticle targeted using the amyloid peptide as a targeting ligand. It was delivered by intracranial injection into the cisterna magna and did not have to negotiate the blood-brain barrier.…”
Section: Introductionmentioning
confidence: 99%
“…To determine how these particles were successful in penetrating the BBB, we conducted [15,16] a subsequent study of BBB permeation of untargeted liposomes in the TetO/APP mouse model of AD. This model features the Swedish and Indiana mutations of the APP gene, under the control of a tetracycline responsive element.…”
Section: Introductionmentioning
confidence: 99%
“…Between the heart and the surface vessels of the brain from which we measured flow and volume signals (Blinder et al, 2010; 2013; Chen et al, 2011) are the large arteries in the circle of Willis (Vrselja et al, 2014), and the initial segments of the large cerebral arteries. These large vessels at the base of the brain contribute a substantial amount to the resistance of the cerebral vascular network (Faraci and Heistad, 1990), allowing them to exert a strong regulatory influence on pressures experienced by downstream vessels in the dorsal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…The results Recent study demonstrated that overproduction of damaged proteins following focal cerebral ischemia increases protein ubiquitination, resulting in ubiquitinated proteins aggregation. 36) Brain ischemia also damages protein degradation pathways, causing the accumulation of ubiquitinated proteins. 37) In this study, we also discovered that Z-ligustilide reduced the accumulation of ubiquitinated proteins induced by both MG132 and OGD-Reoxy and provided the evidence that blocking protein aggregation may be an important mechanism for the protection of Z-ligustilide against OGD-Reoxy induced injury.…”
Section: Discussionmentioning
confidence: 99%